Designing a high school computational thinking test using evidence-centered design - Gomez Valverde, Amadeo Alessandro (2025)
The development of computational thinking as a cognitive skill is essential in this digital age; however, there is still no standard on how to define computational thinking or how to measure it. Therefore, the aim of the research is to develop an instrument that allows the estimation of the level of computational thinking using an evidence-centered design approach. The proposed approach combines cognitive theory, educational research and psychometric modelling to design a comprehensive and reliable assessment framework. The test includes two scenarios with a total of 59 items divided into 6 questions. It was validated by academics related to the scientific field, obtaining a final score of 0.76 as a content validity index. The test was administered to a sample of 100 students from 3 secondary schools in Lima, Peru, and analyzed using Bayesian confirmatory factor analysis and parametric tests. The results showed that the model is suitable for assessing understanding of the dimensions of algorithmic and critical thinking and problem solving, regardless of prior experience with programming languages, while the assessment of creativity requires further adaptation and improvement. This research has implications for the development of evidence-based educational policy and practice in secondary education